A comparison of watershed nitrogen loading and watershed nitrogen exports from on-site wastewater treatment systems and centralized sewer systems in the North Carolina Coastal Plain - Iverson, Guy (East Carolina University, 2013)
Elevated nitrogen (N) concentrations in groundwater may cause adverse effects to adjacent surface water bodies. In North Carolina, half of the residences use on-site wastewater treatment systems (OWTS), yet they are typically not regulated beyond the permitting process. The overall goal of this study was to determine if OWTS affect groundwater N loading and surface water N export at the watershed scale. Eight sub-watersheds were monitored monthly for physical and chemical parameters in Greenville, NC. Four watersheds used OWTS and four watersheds used a centralized sewer system (CSS) that transported wastewater from these watersheds and discharged the treated wastewater to the Tar River. To evaluate the effects of wastewater management on groundwater quality, groundwater was monitored at 10 residential sites, five in an OWTS watershed and five in a CSS watershed. Groundwater samples were collected quarterly for a year (August 2011 to August 2012) and analyzed for dissolved N species (ammonium, nitrate + nitrite, and dissolved organic N) and chloride. Surface water samples were collected monthly and analyzed for the same physical and chemical parameters, including turbidity and particulate N. Groundwater and surface water samples were collected and sent to the Stable Isotope Facility at UC Davis for [delta]¹⁵N and [delta]¹⁸O of nitrate analysis. Groundwater TDN concentrations and loads at OWTS sites were significantly greater than at CSS sites, with mean TDN concentrations in OWTS groundwater up to two times greater and loads up to five times greater than CSS TDN concentrations and loads. Groundwater and surface water stable isotopes, ¹⁵N and ¹⁸O in nitrate, suggested that N sources in OWTS watersheds were wastewater derived, while CSS sources were fertilizer derived. Mean total nitrogen (TN) concentrations in surface water at OWTS watersheds were approximately two times greater than for CSS watersheds during baseflow and storm conditions. Streams draining OWTS watersheds exported significantly greater TN masses than CSS watersheds. Assuming average measured OWTS loads to the soil were representative of each residence in OWTS watersheds, on average OWTS watersheds were found to attenuate 81% (± 14%) of OWTS TN loads to the soil prior to TN export from the watershed. The results from this study illustrate a need for inclusion among nutrient management strategies by North Carolina Department Environment and Natural Resources and other state, federal, and international agencies.
Keywords: Geology; Environmental sciences; Water resources management; Groundwater; Nitrogen; Surface water; Wastewater; Water resources; Water--Nitrogen content--North Carolina; Septic tanks--North Carolina; Sewerage--North Carolina